2020
DOI: 10.1093/ve/veaa026
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of dengue virus type 2 causing outbreaks in Kenya: Evidence of circulation of two cosmopolitan genotype lineages

Abstract: Dengue fever (DF) is an arboviral disease caused by dengue virus serotypes 1-4 (DENV 1-4). Globally, DF incidence and disease burden have increased in the recent past. Initially implicated in a 1982 outbreak, DENV-2 recently reemerged in Kenya causing outbreaks between 2011 and 2014 and more recently 2017–8. The origin and the evolutionary patterns that may explain the epidemiological expansion and increasing impact of DENV-2 in Kenya remain poorly understood. Using whole-genome sequencing, samples collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The BSSVS findings reflected the epidemiological reality of cosmopolitan genotype’s presence in a wide geographical scale 20 , 33 , 54 61 . The most intense virus activity was visible in Southeast Asia, mainly in two epicenters; first, an area covering Singapore, Malaysia and Indonesia and the second centered on Taiwan and China in the Far East.…”
Section: Resultsmentioning
confidence: 71%
“…The BSSVS findings reflected the epidemiological reality of cosmopolitan genotype’s presence in a wide geographical scale 20 , 33 , 54 61 . The most intense virus activity was visible in Southeast Asia, mainly in two epicenters; first, an area covering Singapore, Malaysia and Indonesia and the second centered on Taiwan and China in the Far East.…”
Section: Resultsmentioning
confidence: 71%
“…The BSSVS ndings re ected the epidemiological reality of cosmopolitan genotype's presence in a wide geographical scale [20,33,[52][53][54][55][56][57][58][59]. The most intense virus activity was visible in Southeast Asia, mainly in two epicenters; rst, an area covering Singapore, Malaysia and Indonesia and the second centered on Taiwan and China in the Far East.…”
Section: Resultsmentioning
confidence: 97%
“…In our study covering 2016–2017, DENV-2 was the predominant serotype both before and during the outbreak ( Figure 3 ). A study of febrile patients in CPGH from January 2014 to March 2015 also reported DENV-2 as the predominant serotype, followed by DENV-3 and DENV-1 ( Munyuga et al, 2016 ), as did a study of the outbreaks in 2013–2014 and 2017 based on sequencing results ( Langat et al, 2020 ). Although not observed in this study, outbreaks may coincide with a shift in dengue serotypes ( Bennett et al, 2010 , Gubler, 1998 , Saha et al, 2016 ), and earlier reports, covering the times prior to DENV-2 in circulation, support DENV-1 to be the prevalent serotype in Kenya.…”
Section: Discussionmentioning
confidence: 95%